Fibromyalgia in Spondyloarthritis: Prevalence and Effect on Disease Activity and Treatment - Olfa, Saidane; Bouden, Selma; Sahli, Meriam; Tekaya, Aicha B.; Rouached, Leila; Rawdha, Tekaya; Mahmoud, Ines; Abdelmoula, Leila (Current Rheumatology Reviews, 2023)
Background: Fibromyalgia may be associated to Spondyloarthritis with which it shares some common symptoms such as sleep disorders, fatigue and diffuse pain, leading to diagnostic and treatment dilemmas. Objectives: We aimed to determine the prevalence of fibromyalgia in axial spondyloarthritis and to determine how fibromyalgia might influence the assessments of disease activity and how it might impact treatment. Methods: An observational cross-sectional study was conducted. The study included 100 patients with axial spondyloarthritis according to the Assessment of SpondyloArthritis international Society criteria. Fibromyalgia was diagnosed based on the 2010 American College of Rheumatology criteria. Demographics, disease characteristics, activity parameters and treatment were compared between patients with and without fibromyalgia. Patients were recruited from the hospitalization unit and the outpatient clinic of rheumatology. Results: The mean age of patients was 44.65 ± 13.13 years, with a sex ratio equal to 2. The prevalence of fibromyalgia was 20%. Fibromyalgia associated factors were advanced age and a late age at the onset of axial spondyloarthritis. Disease activity parameters such as global pain VAS, BASDAI, ASDAS-ESR, ASDAS-CRP, BASFI and BAS-G as well as MASES and BASMI were significantly higher in the presence of FM. Doses of paracetamol were significantly higher among FM+ patients. Also, treatment duration of the current anti-TNF alpha agent was significantly shorter among FM+ patients. Conclusion: Our study showed that fibromyalgia was associated with axial spondyloarthritis in 20% of patients. Its presence was associated with higher disease activity parameters and negative impact on the treatment.
Keywords: TNF alpha blockers treatment